Evaluation on the Online Geography Learning Program During the Covid-19 Pandemic Era - Susanthi, Yuli; Nursa'ban, Muhammad (Jurnal Pendidikan dan Pengajaran, 2022)
Online learning was currently applied as a solution for education during the Covid-19 pandemic era in Indonesia. However, several aspects were required to be evaluated to optimally achieve the learning goals. This study was aimed to investigate the implementation of online geography learning at Trenggalek 2 public senior high school using the CIIP evaluation model. The population was geography teachers and social studies class students at the school. Furthermore, the sample was taken using the purposive sampling technique applying the Slovin formula with a significance level of 0.5%. Data were collected through survey and interview methods and then analyzed using quantitative descriptive techniques. Analyzing the context, input, process and product, this research indicated that the online geography learning was well implemented with 75% criteria fulfilled. Therefore, the online learning program could be continued with some improvements.